ICFDA'14 International Conference on Fractional Differentiation and Its Applications 2014 2014
DOI: 10.1109/icfda.2014.6967450
|View full text |Cite
|
Sign up to set email alerts
|

Fractal order evidences in wind speed time series

Abstract: This paper describes some evidence of fractal order features in wind speed time series recorded at different observation stations both in USA and in Italy. Analysis were performed by using mono-fractal, multi-fractal and power spectra approaches. Results show that the average value of the box dimension for daily and hourly mean wind speed is D = 1.19 and D = 1.41 respectively, thus indicating that this kind of time series are fractal. The estimated average value of the Hurst exponent is H = 0.81 and H = 0.75 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Depending on the data set, an analysis on the wind speed characteristics can take place. For instance, in (Fortuna et al [20], 2014), the authors provide a fractal analysis on wind speed observations. Exploitable information can be derived for such analysis for further modeling.…”
Section: Motivation and State-of-the-artmentioning
confidence: 99%
“…Depending on the data set, an analysis on the wind speed characteristics can take place. For instance, in (Fortuna et al [20], 2014), the authors provide a fractal analysis on wind speed observations. Exploitable information can be derived for such analysis for further modeling.…”
Section: Motivation and State-of-the-artmentioning
confidence: 99%
“…Telesca and Lovallo [18] found that most of the multifractality of the wind speed series recorded at several heights from the ground from 50m to 213m was due to the different long-range correlations in small and large speed fluctuations. Fortuna et al [19] applied the MFDFA to several hourly wind speed series in Italy and USA and found that the multifractal width ranged in a quite close interval of values between 0.39 and 0.59. De Figueiredo et al [20] found that the mean and the maximum of four wind speed time series in Brazil were all persistent, but the maximum was more multifractal than the mean.…”
mentioning
confidence: 99%
“…Recently, Cadenas et al [24] compared the predictive capacity of a univariate ARIMA model for wind speed against a nonlinear autoregressive exogenous model (NARX) model using as input the wind direction, temperature, pressure, solar radiation, relative humidity and speed of the wind. The main assumption of the statistical methods is that these assume a family of underlying stochastic processes that are generally stationary, linear and homoscedastic, but most of the time series analyzed do not comply with these restrictions, since they have characteristics of heteroscedasticity and present long-term dependencies [7,8].…”
Section: Methodsmentioning
confidence: 99%